Adhesive composition and adhesive film

By using an adhesive composition containing an aromatic group (meth)acrylate base polymer and a high refractive index additive in a high refractive index light/thermal curing adhesive film, the problems of insufficient refractive index and low adhesive strength of the conventional adhesive film are solved, and an adhesive film with high refractive index, excellent optical characteristics and excellent mechanical properties are achieved.

CN118978883BActive Publication Date: 2025-04-18GUANGDONG CROWN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411122217.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-04-18
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The traditional high-refractive index light/thermal curing adhesive film has insufficient refractive index and low bonding strength, which cannot meet the high optical performance and mechanical performance requirements in the fields of photovoltaics, photoelectric display devices, etc.

Method used

A binder composition containing an aromatic group-containing (meth)acrylate base polymer and a high refractive index additive is used, and the high refractive index additive is a chemical with a refractive index of 1.65 or more, including a mixture of a fluorene compound having a substituent group and a dinaphthiophene compound.

Benefits of technology

The performance of high-refractive index adhesive film has been achieved, with a refractive index of more than 1.55, and both Haze and b* are below 1.2. At the same time, the mechanical strength and adhesive force have been improved, and are suitable for photovoltaics, photoelectric displays and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004995411040000021
    Figure BDA0004995411040000021
  • Figure BDA0004995411040000091
    Figure BDA0004995411040000091
  • Figure BDA0004995411040000092
    Figure BDA0004995411040000092
Patent Text Reader

Abstract

The present invention provides an adhesive composition, the adhesive composition is a base polymer comprising at least one (meth)acrylate containing an aromatic group and a high refractive index additive, the high refractive index additive is a chemical with a refractive index of 1.65 or more, the content of the high refractive index additive is 20 or more and 60 or less when the content of the base polymer is 100, the refractive index of the adhesive composition is 1.55 or more, the Haze is 1.2 or less, and the b* is 1.2 or less. The present invention achieves a comprehensive leap in the performance of the high refractive index adhesive film through innovative formula design and preparation process, bringing significant technological progress and industrial upgrading to the photovoltaic and optoelectronic display fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesive compositions, in particular to a high-refractive-index adhesive and an adhesive film. Background Art

[0002] High refractive index adhesives and adhesive films are increasingly used in photovoltaic and optoelectronic display devices. However, traditional high refractive index light / heat curing adhesive films face significant challenges: their refractive index generally fails to reach the ideal height, and the bonding strength is insufficient to meet the actual use requirements of the product. This is mainly due to the limitations of existing technologies in the selection of high refractive index monomers, fillers, and interface bonding with substrates.

[0003] Specifically, the refractive index of similar high-refractive index adhesive films on the market generally hovers in the range of 1.50 to 1.60, which is difficult to meet the growing demand for higher optical performance. In addition, the mechanical properties of these materials, especially the bonding strength, are relatively low. Therefore, it has become an urgent need in this field to develop a high-refractive index adhesive film with both a higher refractive index and better mechanical properties to achieve a significant increase in refractive index. Summary of the invention

[0004] The present invention aims to provide an adhesive and an adhesive film, and through innovative formula design and preparation process, achieve a comprehensive leap in the performance of a high refractive index adhesive film, bringing significant technological progress and industrial upgrading to the photovoltaic and optoelectronic display fields.

[0005] In order to achieve the above-mentioned object, the present invention provides an adhesive composition, which is a base polymer comprising at least one (meth)acrylate containing an aromatic group and a high refractive index additive, wherein the high refractive index additive is a chemical with a refractive index of 1.65 or more, and the content of the high refractive index additive is between 20 and 60 when the content of the base polymer is 100. The refractive index of the adhesive composition is above 1.55, the Haze is below 1.2, and the b* is below 1.2.

[0006] Furthermore, the high refractive index additive is a mixture containing at least one fluorene compound (A) having a substituent and at least one dinaphthothiophene compound (B) having a substituent.

[0007] Furthermore, the high refractive index additive comprises at least one fluorene compound (A) having a refractive index of 1.65 or more and having a substituent and at least one dinaphthothiophene compound (B) having a refractive index of 1.7 or more and having a substituent.

[0008] Furthermore, the content of the substituted fluorene compound (A) in the high refractive index additive is 5 or more and 40 or less when the base polymer content is 100, and the content of the substituted dinaphthothiophene compound (B) is 5 or more and 50 or less when the base polymer content is 100.

[0009] Furthermore, the content of the aromatic ring monomer in the base polymer of the aromatic group-containing (meth)acrylate is greater than 30 wt % and less than 75 wt %.

[0010] Furthermore, the base polymer of the (meth)acrylate containing an aromatic group comprises

[0011] Compound of formula 1:

[0012]

[0013] wherein X is a single bond, a C1 to C5 alkylene group, or an oxygen atom;

[0014] Y is a hydrogen atom or a methyl group;

[0015] R1 is C1 to C10 alkyl, halogen or C6 to C20 aryl;

[0016] n is an integer from 0 to 5; and

[0017] R2 is a C1 to C10 alkylene group or a C1 to C30 polyalkylene group or an oxygen atom.

[0018] In addition, the present invention also provides an adhesive film, comprising an adhesive layer formed by the above adhesive composition.

[0019] Compared with the prior art, the present invention provides a novel adhesive that combines high refractive index, excellent optical properties and excellent viscosity. The core composition of the adhesive cleverly combines carefully selected base polymers with high-performance high-refractive index additives to achieve a significant improvement in material performance. Through the original adhesive composition of this patent, the adhesive film prepared not only successfully achieves the goal of high refractive index, but also maintains excellent optical transparency while giving it excellent mechanical strength and adhesion, providing innovative solutions for optoelectronics, optical instruments and high-end display technology. DETAILED DESCRIPTION

[0020] Example 1

[0021] (Preparation of polymer)

[0022] In a 4-mouth glass reactor equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler, a monomer mixture was added, including 30 parts by weight of n-butyl acrylate, 65 parts by weight of m-phenylbenzyl acrylate (POBA), and 5 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.2 parts by weight of polymerization initiator 2,2'azobisisobutyronitrile (AIBN), and 150 parts by weight of polymerization solvent ethyl acetate. Then, the mixture was slowly stirred and nitrogen was introduced. The temperature in the reactor was maintained at about 60°C, and the polymerization reaction was carried out for 6 hours to prepare a P1 polymer solution (polymer concentration 40%). The Mw of the P1 polymer was 500,000.

[0023] (Preparation of adhesive composition)

[0024] The aforementioned P1 polymer solution (polymer concentration 40%) was diluted to 20% with ethyl acetate. To 500 parts by weight of the solution (containing 100 parts by weight of the P1 polymer), 5 parts by weight of bisphenol fluorene (refractive index 1.68), 30 parts by weight of 6-methoxymethyl dinaphthothiophene (refractive index 1.75), and 0.05 parts by weight of a crosslinking agent trimethylolpropane / xylylene diisocyanate additive (Mitsui Chemicals, trade name [Takenate D-110N], solid content 75%) were added as a solid content basis. After stirring and mixing, the adhesive shown in this example was obtained.

[0025] (Making adhesive film)

[0026] The prepared adhesive composition is applied on the silicon-coated surface of the silicon-coated PET film R1 (thickness 50 μm), and heated at 130°C for 2 minutes to form a 25 μm adhesive layer. After that, the silicon-coated surface of the silicon-coated PET film R2 (thickness 25 μm) is attached to the surface of the aforementioned adhesive layer. After completion, a substrate-free double-sided adhesive film composed of the aforementioned adhesive can be obtained. Both sides of the adhesive film are protected by PET films (release films) R1 and R2.

[0027] Example 2

[0028] (Preparation of Polymer)

[0029] In a 4-mouth glass reactor equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler, a monomer mixture was added, including 30 parts by weight of n-butyl acrylate, 65 parts by weight of m-phenylbenzyl acrylate (POBA), and 5 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.2 parts by weight of polymerization initiator 2,2'azobisisobutyronitrile (AIBN), and 150 parts by weight of polymerization solvent ethyl acetate. Then, the mixture was slowly stirred and nitrogen was introduced. The temperature in the reactor was maintained at about 60°C, and the polymerization reaction was carried out for 6 hours to prepare a P1 polymer solution (polymer concentration 40%). The Mw of the P1 polymer was 500,000.

[0030] (Preparation of adhesive composition)

[0031] The aforementioned P1 polymer solution (polymer concentration 40%) was diluted to 20% with ethyl acetate. 7 parts by weight of bisphenol fluorene (refractive index 1.68), 25 parts by weight of 6-methoxymethyl dinaphthothiophene (refractive index 1.75), and 0.05 parts by weight of a crosslinking agent trimethylolpropane / xylylene diisocyanate additive (Mitsui Chemicals, trade name [Takenate D-110N], solid content 75%) were added as a solid content basis to 500 parts by weight of the solution (containing 100 parts by weight of the P1 polymer). The adhesive shown in this example was obtained by stirring and mixing.

[0032] (Making adhesive film)

[0033] The prepared adhesive composition is applied on the silicon-coated surface of the silicon-coated PET film R1 (thickness 50 μm), and heated at 130°C for 2 minutes to form a 25 μm adhesive layer. After that, the silicon-coated surface of the silicon-coated PET film R2 (thickness 25 μm) is attached to the surface of the aforementioned adhesive layer. After completion, a substrate-free double-sided adhesive film composed of the aforementioned adhesive can be obtained. Both sides of the adhesive film are protected by PET films (release films) R1 and R2.

[0034] Example 3

[0035] (Preparation of Polymer)

[0036] In a 4-mouth glass reactor equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler, a monomer mixture was added, including 30 parts by weight of n-butyl acrylate, 65 parts by weight of m-phenylbenzyl acrylate (POBA), and 5 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.2 parts by weight of polymerization initiator 2,2'azobisisobutyronitrile (AIBN), and 150 parts by weight of polymerization solvent ethyl acetate. Then, the mixture was slowly stirred and nitrogen was introduced. The temperature in the reactor was maintained at about 60°C, and the polymerization reaction was carried out for 6 hours to prepare a P1 polymer solution (polymer concentration 40%). The Mw of the P1 polymer was 500,000.

[0037] (Preparation of adhesive composition)

[0038] The aforementioned P1 polymer solution (polymer concentration 40%) was diluted to 20% with ethyl acetate. 10 parts by weight of bisphenol fluorene (refractive index 1.68), 35 parts by weight of 6-methoxymethyl dinaphthothiophene (refractive index 1.75), and 0.05 parts by weight of a crosslinking agent trimethylolpropane / xylylene diisocyanate additive (Mitsui Chemicals, trade name [Takenate D-110N], solid content 75%) were added as a solid content basis to 500 parts by weight of the solution (containing 100 parts by weight of the P1 polymer). The adhesive shown in this example was obtained by stirring and mixing.

[0039] (Making adhesive film)

[0040] The prepared adhesive composition is applied on the silicon-coated surface of the silicon-coated PET film R1 (thickness 50 μm), and heated at 130°C for 2 minutes to form a 25 μm adhesive layer. After that, the silicon-coated surface of the silicon-coated PET film R2 (thickness 25 μm) is attached to the surface of the aforementioned adhesive layer. After completion, a substrate-free double-sided adhesive film composed of the aforementioned adhesive can be obtained. Both sides of the adhesive film are protected by PET films (release films) R1 and R2.

[0041] Comparative Example 1

[0042] (Preparation of polymer)

[0043] In a 4-mouth glass reactor equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler, a monomer mixture was added, including 30 parts by weight of n-butyl acrylate, 65 parts by weight of m-phenylbenzyl acrylate (POBA), and 5 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.2 parts by weight of polymerization initiator 2,2'azobisisobutyronitrile (AIBN), and 150 parts by weight of polymerization solvent ethyl acetate. Then, the mixture was slowly stirred and nitrogen was introduced. The temperature in the reactor was maintained at about 60°C, and the polymerization reaction was carried out for 6 hours to prepare a P1 polymer solution (polymer concentration 40%). The Mw of the P1 polymer was 500,000.

[0044] (Preparation of adhesive composition)

[0045] The aforementioned P1 polymer solution (polymer concentration 40%) was diluted to 20% with ethyl acetate. 35 parts by weight of bisphenol fluorene (refractive index 1.68) and 0.05 parts by weight of a crosslinking agent trimethylolpropane / xylylene diisocyanate additive (Mitsui Chemicals, trade name [Takenate D-110N], solid content 75%) were added to 500 parts by weight of the solution (containing 100 parts by weight of the P1 polymer) as a solid content standard. After stirring and mixing, the adhesive shown in this example was obtained.

[0046] (Making adhesive film)

[0047] The prepared adhesive composition is applied on the silicon-coated surface of the silicon-coated PET film R1 (thickness 50 μm), and heated at 130°C for 2 minutes to form a 25 μm adhesive layer. After that, the silicon-coated surface of the silicon-coated PET film R2 (thickness 25 μm) is attached to the surface of the aforementioned adhesive layer. After completion, a substrate-free double-sided adhesive film composed of the aforementioned adhesive can be obtained. Both sides of the adhesive film are protected by PET films (release films) R1 and R2.

[0048] Comparative Example 2

[0049] (Preparation of polymer)

[0050] In a 4-mouth glass reactor equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler, a monomer mixture was added, including 30 parts by weight of n-butyl acrylate, 65 parts by weight of m-phenylbenzyl acrylate (POBA), and 5 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.2 parts by weight of polymerization initiator 2,2'azobisisobutyronitrile (AIBN), and 150 parts by weight of polymerization solvent ethyl acetate. Then, the mixture was slowly stirred and nitrogen was introduced. The temperature in the reactor was maintained at about 60°C, and the polymerization reaction was carried out for 6 hours to prepare a P1 polymer solution (polymer concentration 40%). The Mw of the P1 polymer was 500,000.

[0051] (Preparation of adhesive composition)

[0052] The aforementioned P1 polymer solution (polymer concentration 40%) was diluted to 20% with ethyl acetate. 50 parts by weight of 6-methoxymethyl dinaphthothiophene (refractive index 1.75) was added to 500 parts by weight of the solution (containing 100 parts by weight of the P1 polymer), and 0.05 parts by weight of a crosslinking agent trimethylolpropane / xylylene diisocyanate additive (Mitsui Chemicals, trade name [Takenate D-110N], solid content 75%) was added as a solid content basis. After stirring and mixing, the adhesive shown in this example was obtained.

[0053] (Making adhesive film)

[0054] The prepared adhesive composition is applied on the silicon-coated surface of the silicon-coated PET film R1 (thickness 50 μm), and heated at 130°C for 2 minutes to form a 25 μm adhesive layer. After that, the silicon-coated surface of the silicon-coated PET film R2 (thickness 25 μm) is attached to the surface of the aforementioned adhesive layer. After completion, a substrate-free double-sided adhesive film composed of the aforementioned adhesive can be obtained. Both sides of the adhesive film are protected by PET films (release films) R1 and R2.

[0055] Comparative Example 3

[0056] (Preparation of polymer)

[0057] In a 4-mouth glass reactor equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler, a monomer mixture was added, including 95 parts by weight of m-phenylbenzyl acrylate (POBA), 5 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.2 parts by weight of polymerization initiator 2,2'azobisisobutyronitrile (AIBN), and 150 parts by weight of polymerization solvent ethyl acetate. Then, the mixture was slowly stirred and nitrogen was introduced. The temperature in the reactor was maintained at about 60°C, and the polymerization reaction was carried out for 6 hours to prepare a P2 polymer solution (polymer concentration 40%). The Mw of the P2 polymer was 450,000.

[0058] (Preparation of adhesive composition)

[0059] The aforementioned P2 polymer solution (polymer concentration 40%) was diluted to 20% with ethyl acetate. To 500 parts by weight of the solution (containing 100 parts by weight of the P2 polymer), 5 parts by weight of bisphenol fluorene (refractive index 1.68), 10 parts by weight of 6-methoxymethyl dinaphthothiophene (refractive index 1.75), and 0.05 parts by weight of a crosslinking agent trimethylolpropane / xylylene diisocyanate additive (Mitsui Chemicals, trade name [Takenate D-110N], solid content 75%) were added as a solid content basis. After stirring and mixing, the adhesive shown in this example was obtained.

[0060] (Making adhesive film)

[0061] The prepared adhesive composition is applied on the silicon-coated surface of the silicon-coated PET film R1 (thickness 50 μm), and heated at 130°C for 2 minutes to form a 25 μm adhesive layer. After that, the silicon-coated surface of the silicon-coated PET film R2 (thickness 25 μm) is attached to the surface of the aforementioned adhesive layer. After completion, a substrate-free double-sided adhesive film composed of the aforementioned adhesive can be obtained. Both sides of the adhesive film are protected by PET films (release films) R1 and R2.

[0062] Table 1 - Polymer solutions in examples and comparative examples of adhesive compositions

[0063]

[0064] Table 2 - Examples of adhesive compositions, comparative examples and properties of adhesive films prepared therefrom

[0065]

[0066] The above embodiments do not impose any limitation on the content of the composition of the present invention. Any slight modification, equivalent change and modification made to the above embodiments based on the technical essence or composition ingredients or content of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. An adhesive composition, comprising a base polymer comprising at least one (meth)acrylate containing an aromatic group and a high refractive index additive, wherein the high refractive index additive comprises at least one fluorene compound (A) having a refractive index of 1.65 or more and having a substituent and at least one dinaphthothiophene compound (B) having a refractive index of 1.7 or more and having a substituent, wherein the content of the high refractive index additive is 20 or more and 60 or less based on the content of the base polymer as 100, and the refractive index of the adhesive composition is 1.55 or more, Haze is 1.2 or less, and b* is 1.2 or less; The content of the aromatic ring monomer in the base polymer of the (meth)acrylate containing an aromatic group is greater than 30 wt % and less than 75 wt %. The base polymer of the (meth)acrylate containing an aromatic group comprises a compound of Formula 1: wherein X is a single bond, a C1 to C5 alkylene group, or an oxygen atom; Y is a hydrogen atom or a methyl group; R1 is C1 to C10 alkyl, halogen or C6 to C20 aryl; n is an integer from 0 to 5; and R2 is a C1 to C10 alkylene group or a C1 to C30 polyalkylene group or an oxygen atom.

2. The adhesive composition according to claim 1, characterized in that The content of the substituted fluorene compound (A) in the high refractive index additive is 5 or more and 40 or less based on 100 of the base polymer content, and the content of the substituted dinaphthothiophene compound (B) is 5 or more and 50 or less based on 100 of the base polymer content. 3 . An adhesive film comprising an adhesive layer formed from the adhesive composition according to claim 1 or 2 .

Citation Information

Patent Citations

  • Resin composition for coating materials

    CN104350111A

  • Adhesive composition, adhesive, and adhesive sheet

    CN115335480A